Sophistication in a seemingly simple creature: a review of wild holothurian nutrition in marine ecosystems. (13th October 2021) - Pierrat, Joséphine; Bédier, Alexandre; Eeckhaut, Igor; Magalon, Hélène; Frouin, Patrick
ABSTRACT: Holothurians are marine invertebrates that are among the most widespread benthic megafauna communities by both biomass and abundance in shallow‐water and deep‐sea ecosystems, their functions supporting important ecological services worldwide. Despite their simple appearance as sea cucumbers, holothurians show a wide range of feeding practices. However, information on what and how these animals eat is scattered and potentially confusing. We provide a comprehensive review of holothurian nutrition in coastal and deep‐sea ecosystems. First, we describe morphological aspects of holothurian feeding and the ultrastructure of tentacles. We discuss the two processes for food capture, concluding that mucus adhesion is likely the main method; two mucous cells, type‐1 and type‐2, possibly allow the adhesion and de‐adhesion, respectively, of food particles. Secondly, this review aims to clarify behavioural aspects of holothurian suspension‐ and deposit‐feeding. We discuss the daily feeding cycle, and selective feeding strategies. We conclude that there is selectivity for fine and organically rich particles, and that feeding through the cloaca is also a route for nutrient absorption. Third, we provide a wide description of the diet of holothurians, which can be split into two categories: living and non‐living material. We suggest that Synallactida, Molpadida, Persiculida, Holothuriida and Elasipodida, ingest the same fractions, and emphasise the importance of bacteria in the diet of holothurians.